TACS in the development of reading skills - Zambrano García, Lourdes Beatriz; Vélez Villavicencio, Carlina (Revista Minerva, 2023)
From a creative perspective in the educational field, along with the digital age, it is necessary to promote the use of Learning and Knowledge Technologies, TACS in the development of reading skills, through the innovation of classroom processes. and the discovery of the benefits provided by technology-mediated tools. The objective of the research was to identify the use of TACS in the development of reading skills in elementary level students of District 13D12 of Tosagua canton, Ecuador; from a qualitative, exploratory and descriptive approach. The technique used was participant observation to assess the development of skills in the research scenario chosen in two moments; in the first, a reading comprehension exercise was applied in a traditional way and a second moment using the TACS. The main results determine that the use of the TACS favorably affects the development of reading skills in an innovative and attractive way for students, allowing the teacher to promote active listening and paraphrasing. In this way, it is concluded that, by involving technological, digital resources in the classroom, students develop cognitive skills related to reading.